Tingkat Pemahaman Peserta Didik tentang Tugas-tugas Perkembangan Sosial Remaja di Kelas X SMK Negeri 6 Padang - Novita, Rita; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
Background o this research is level of comprehension students about social development assigment teenager. Base on the researcherâs observation in SMK N 6 Padang at 2st September 2013 that teenager less understand about their assignment as teenager and teenager less comprehension about social development assigment teenager. So, many experience problems students such as: students less polite in speak, students choose riend in relationsip, students not able to make good connection with different gendre, students not polite to teacher, students disparage to teacher and their expand: 1) level of students comprehension about development comprehension in guide good connection with member group. 2) level of students comprehension about development assigment. This research is kuantitatif describtive research the researcher decided totake the data by using simple random sampling technique. Sample of this research is students and the students as main respondent the total students 79 addition. Respondent is counselor teacher and subject teacher. The instrumentation in this research is questionnaire. While data analysis uses percentage technique. The result of this research are: 1). Level of comprehension students about social development teenager in guide good connection with member group in low category 83, 54% from respondent. 2). Level of comprenhension students about social development assigment teenager in social duty development in high category 81,01% from respondent.